Necessary improvements in the legal framework of private house construction - Riabova, Katerina (Riga Graduate School of Law, 2019)
The work will investigate contractual, legal and process regulation in the field of private house construction in Latvia. The aim is to assess the feasibility of developing an alternative model for the private house construction industry that is in line with internationally accepted norms and standards. The paper focuses on industry standardization and the improvements needed for it: changes in regulatory frameworks, choice of standard contracts and standards, as well as insurance issues insofar as they involve risks associated with private house construction and the introduction of a more efficient procurement mechanism.
Keywords: Research Subject Categories::LAW/JURISPRUDENCE::Other law::European law; Construction law; Latvia